Metodología para reducir las pérdidas técnicas en las redes de distribución de media tensión con aplicación en el circuito industrial norte (2005)
The importance that has the development of this study is extremely important in many aspects, especially in the economic profitability that there would obtain the distribution companies that in this case it concerns Electricaribe; because a bad handling that is given to the topic of the technical losses would cause problems of financial type in the company and as for the efficiency and quality with which it gives the electric power service. To realize a study in decrease of technical losses is not easy at all, especially when he does not get ready of all the real information that would be needed to develop the above mentioned study; that's why the methodology proposed in this work offers the best election that the distribution companies must choose if they want to increase its economic profitability. Nevertheless it is necessary to note down that the technical losses cause losses of money to the companies and hence towards the clients, who must pay in the end for a given service. To finish one concludes that if the distribution companies do not realize investments in studies and application of decrease in losses there will never be efficient, profitable and highly competitive companies.